Structure and characterisation as metaphors for neurological disorder in Chris Abani's Graceland - Ohwovoriole, Benjamin Cyril Oghenekaro (My University, 2010)
ABSTRACT Graceland is a figurative narrative. Although the writer grapples with ideas of national identity and relations of power, the text primarily comes across as a vivid metaphor that stirs disturbing imagery of a particular nation. Chris Abani achieves this through the structure of the novel and the characterisation he employs. In Graceland, Chris Abani draws the reader’s attention to the nature of the post-colony through a country that became independent politically in 1960. His submission, in this fictive work, is that Nigeria is a fractured nation 45 years on. There are tensions within the polity, resulting in instability and anarchy of values. This tragedy is dramatised through the lives of the ordinary people, but it poignantly suggests the failure of the elite, who are largely silent in Graceland, but callously omniscient in the text. In this work, I examine how the writer, amongst other things, aestheticises the broken nature of the post-colonial African state in the 21st century. This study is salient because Chris Abani belongs to the generation of Nigerian writers, whose sensibilities have been influenced by a socio-political environment largely different from those that have inspired the writings of the first and second waves of Nigerian writers, who populated Nigeria’s literary landscapes of the 60s and 80s.